CHRONIC MYCOTIC-ASSOCIATED SURGICAL NAIL PATHOLOGY COMPLICATED WITH INGROWN NAIL (NAIL INCARNATION): THE ANALYSES OF CLINICAL CASES AND COMPLEX TREATMENT - Vergun, A. R.; Parashchuk, B. M.; Krasny, M. R.; Kit, Z. M.; Vergun, O. M. (International Journal of Medicine and Medical Research, 2017)
Background. Conservative treatment of secondary recurrent unguis incarnatus are not very effective and Dupuytren’s method, Emmert-Schmiden surgeries etc. are very traumatic, disfigure nail bone, distort anatomic and functional unity of a nail. Objective. The aim of our research was the optimal sequence of holiatry, surgical moving away from nails, local and system therapy after excision of the staggered nails in case of destructive onychomycosis complicated by secondary ingrown nail for some patients with complicated mycotic defeat of nails. Clinical options of surgical treatment were clarified; morphologic changes were studied; causes of unsatisfactory outcomes of chronic pathology complex treatment were analyzed for prospective approaches to preventing of relapses. Methods. The analysis justifies the feasibility of establishing of predictive relationships between clinical variants of chronic purulent necrotic infections and combined comorbidity. System therapy by itraconazole before operative treatment (basic onychial defeats sanation) and in a postoperative period was carried out. Types of operative treatment applied may be divided into five statistic groups. Results. Over a five-year period (2010-2015) 436 unguis incarnates diagnosis (325 cases of incarnated onychomycosis) in 259 men and 177 women aged 12-67 were performed, 38 of them with incarnated onychogryphosis had diabetes mellitus and 24 had metabolic syndrome. Analysis of subonychial scraping allowed stating the prevalence of red trichophytia in 31% of cases with the bacterial flora. Patients with combined pathology got 4-5 five-day system ‘pulses’ of 400 mg/day itraconazole therapy. In patients with primary advantage of providing low-impact methods of nail excision with access via onycholisation structure a nail extirpation and marginal matricectomy was carried out; dermatophytoms and stratification on a nail bed were deleted. Conclusions. Type of onychectomy wound cytograms in the study group on the 10th day was defined as regenerative-inflammatory in 24.81%, regeneratory in 75.19% (p=0.031). The methods of surgical treatment of mycotical recurrent nail incarnation have been improved considering patho- and morphogenetic properties of destructive onychomycosis.